Resistance through Solidarity of Sisterhood in Anne Bronte’s Agnes Grey - Bhusal, Damodar (Vox Batauli, 2023)
The paper attempts to examine the resistance against cruel patriarchy through the solidarity of sisterhood in Anne Bronte’s Agnes Grey. The major character, Agnes, faces many obstacles while she works as governess especially in Mr. Bloomfield’s house. The paper concerns itself how the female characters such as Agnes, Miss Murray, Mrs. Murray, Mrs. Agnes and Mary are united with their female bonding and solidarity and resist the male prejudice. In doing so, it specifically utilizes the idea of Ann Jefferson’s (2022) idea of female friendship, female bonding and solidarity through sisterhood and of course the major premises of feminism in general. The paper is divided into four parts. In the first part introduces the issue and reviews major works on sisterhood and feminism. The second part presents its methodology. As its methodology, it utilizes the third part presents results and the final part presents discussion. The paper concludes that the male brutalities against women can be prevented if women remain united. The purpose of female bonding, moreover, is not to replace the patriarchy with matriarchy but to establish equality.